A new name for Amphibolips kinseyi Cuesta-Porta & Pujade-Villar and a revised key to the Amphibolips ‘nassa’ species-complex from Mexico and Central America (Hymenoptera: Cynipidae) - Cuesta-Porta, Víctor; Melika, George; Equihua-Martínez, Armando; Estrada-Venegas, Edith G.; Cibrián-Tovar, David; Barrera-Ruíz, Uriel M.; Silva, Salvador Ordaz; Sánchez, Imelda Virginia López; Pujade-Villar, Juli (Zootaxa, 2021)
Three days before the paper “Revision of the Amphibolips species of the ‘nassa’ species-complex from Mexico and Central America (Hymenoptera: Cynipidae)” was published in Zootaxa, another paper describing three new Amphibolips species from Mexico was published in ZooKeys. As a result, two different species have been described under the same name, ‘Amphibolips kinseyi’. To solve this homonymy, a new name Amphibolips comini Cuesta-Porta & Pujade-Villar, nom. nov. is proposed for replacing A. kinseyi Cuesta-Porta & Pujade-Villar, 2020, a junior homonym of A. kinseyi Nieves-Aldrey & Castillejos-Lemus, 2020. Accordingly, new keys for adults of the Amphibolips ‘nassa’ species-complex and their associated host galls, including all known species from Mexico and Central America are provided.